Assessment of heavy metal accumulations and health risk potentials in tomatoes grown in the discharge area of a municipal wastewater treatment plant - Arslan Topal, E. Isil; Topal, Murat; Obek, Erdal (Taylor & Francis Ltd, 2022)
Some heavy metals were detected in organs of the tomatoes grown in the discharge area of effluents of a municipal wastewater treatment plant. Also, the health risk potentials of heavy metals in the tomatoes consumed by human were investigated. The highest concentrations for Cu, Ni, Cr, Mn and Pb were followed the order of root>leaf>stem>fruit. When the bioconcentration factors values calculated for bioconcentration of metals from effluent to stem and root were examined, the highest values were determined for Cu. When translocation factors values are examined, the highest translocation from root to leaf was determined for Cd. The highest translocation from stem to leaf was determined for Pb. The estimated total exposure dose for male, female and children was listed as Zn>Mn>Cu>Cr>Ni>Pb>Cd. In terms of dietary, we can list the non-carcinogenic risks of heavy metals as children> female> male. The highest carcinogenic risk was calculated for Cr via dietary intake.
Keywords: Accumulation; health; heavy metals; risk; tomato; wastewater